2022
DOI: 10.1097/qai.0000000000003089
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: HIV Infection Does Not Explain Higher Nicotine Metabolism in People Living With HIV

Abstract: Background: Smoking contributes to significant morbidity and mortality in people with HIV. People with HIV have relatively high nicotine metabolism rates, as measured by the nicotine metabolite ratio (NMR, 3-hydroxycotinine/cotinine). A higher NMR is associated with difficulty quitting smoking. We hypothesized that HIV infection might upregulate nicotine metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…Our team has previously found that PWH who smoke have a higher NMR than those without HIV who smoke 8 . Although we found that HIV infection itself (i.e., pre‐ vs. post‐HIV infection change in NMR) does not appear to be the mechanism responsible for the higher NMR in PWH who smoke, 9 we did find a small increase in the NMR after viral suppression (0.14, P = 0.002). However, there was a marked increase for those taking efavirenz‐based regimens (0.53, P < 0.001) 10 .…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Our team has previously found that PWH who smoke have a higher NMR than those without HIV who smoke 8 . Although we found that HIV infection itself (i.e., pre‐ vs. post‐HIV infection change in NMR) does not appear to be the mechanism responsible for the higher NMR in PWH who smoke, 9 we did find a small increase in the NMR after viral suppression (0.14, P = 0.002). However, there was a marked increase for those taking efavirenz‐based regimens (0.53, P < 0.001) 10 .…”
Section: Discussioncontrasting
confidence: 77%
“…We previously demonstrated that HIV acquisition had no discernable effect on the NMR. 9 In contrast, specific ART medications may alter the NMR through effects on CYP2A6. Efavirenz, a key component of ART globally, may upregulate CYP2A6 10 (CYP2A6 contributes to efavirenz metabolism) as it does CYP2B6, the primary enzyme involved in its metabolism.…”
Section: How Might This Change Clinical Pharma-cology or Translationa...mentioning
confidence: 99%
See 1 more Smart Citation